Envenomation by the Malagasy colubrid snake Langaha madagascariensis - NC D'Cruze (Journal of Venomous Animals and Toxins including Tropical Diseases, 2008)
This report documents a case of envenomation by a Malagasy opisthoglyphous snake, Langaha madagascariensis. The snake bit the finger of a healthy adult man who was attempting to record its morphological measurements as part of a biodiversity survey which was being conducted in the extreme north of Madagascar. Symptoms of this case included severe local pain accompanied by observable swelling which lasted for several days. The present observations indicate that bite by L. madagascariensis potentially causes notable physiological effects in humans although the snake is generally calm and reluctant to bite unless provoked.